Evaluating communication protocols for miniature wireless sensor devices - Poon, Wen Jie. (2011)
Wireless sensor devices are commonly used for monitoring physical and environmental phenomena, and are often constrained in size due to mobility requirements. Their miniature size results in a drastic decrease in the battery capacity available, thus these devices typically run on a single radio transceiver.